Automation of the reading and interpretation of the OTDR plot - MAZOUZI, Amine; ABOUN ABID, Miloud (University of Eloued جامعة الوادي, 2022)
Unlike conventional networks, optical fiber transmission systems allow optical signals to be transported from the transmitter to the receiver. They have become the adaptable solution for transmissions of all types of data. By taking into account the problems and the external constraints which degrade the quality of the transmitted signal, the monitoring of the optical fibers is carried out by measurement tools making it possible to detect the various events and the defects along the fiber and this in order to do the maintenance. Necessary to provide better transmission on the medium. Currently the operation of monitoring an optical transmission link is carried out by an agent who constantly monitors the various changes in events that have occurred in the layout of the transmission line using OTDR equipments.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Fiber optic link, OTDR, maintenance, automation, wavelets